The role of Cysteinyl leukotriene receptor-1 during experimental helminth infections in murine model - Mosala, Paballo Pertunia (Department of Clinical Laboratory Sciences, 2021)
Cysteinyl leukotrienes (cysLTs) are potent inflammatory lipid mediators that play a major role in the pathophysiology of inflammatory diseases. They signal primarily through cysteinyl leukotriene receptor-1 (cysLTR1) and have been reported to drive Th2 immune responses. Initiation and amplification of robust Th2 immune responses is crucial for conferring protective immunity to helminth (Schistosoma mansoni and Nippostrongylus brasiliensis) infection in mice. The role played by cysLTs in the development of protective immune responses to helminth infections is not well documented. Hence in the present study, we investigated the role of cysLTs during helminth infection using cysteinyl leukotriene receptor-1 deficient (cysLTR1-/- ) mice. Under steady state conditions, young naïve cysLTR1-/- mice did not reveal any significant alteration of the cellular, tissue and phenotypic profile although we did observe expansion of central memory T cells (Tcm) in secondary lymphoid organs in cysLTR1-/- as compared to wildtype mice. Primary infection with N. brasiliensis indicated increased worm burden in cysLTR1-/- mice at day 7 post infection and a delay in the resolution of infection by day 9 post infection when compared to wild type mice. Furthermore, we observed reduced Th2 immune responses as well as impaired contractility of the small intestine, which are key features required for protective immunity to N. brasiliensis infection. Furthermore, recall of memory responses to N. brasiliensis was abrogated in cysLTR1 -/- mice, with higher numbers of adult worms recovered at day 5 post re-infection in cysLTR1-/- mice comparison with wild type mice. Additionally, cysLTR1-/- mice exhibited impaired production of IL-13 in the lungs and draining lymph nodes compared with wildtype mice. Finally, there was reduced recruitment of effector CD4+ T cells and central memory CD4+ T cells in the lungs of cysLTR1 deficient mice compared to control mice. Taken together, these data demonstrated an essential role played by cysLTR1 in clearance and resolution of N. brasiliensis infection. CysLTR1-/- mice survived acute S. mansoni infection similarly to wildtype mice. In addition, cysLTR1-/- mice displayed reduced granulomatous inflammation and reduced cellular responses in the liver compared with wildtype mice. Further analysis revealed reduced gut fibrosis but cytokine production, immune cell recruitment in the gut and both type 1 and type 2 antibodies were found to be comparable between wildtype and knockout mice, demonstrating that cysLTs signaling through cysLTR1 contribute to granuloma formation in the liver. Similar to acute schistosomiasis, cysLTR1-/- mice were not susceptible to chronic schistosomiasis and indicated by prolonged host survival. This increased host survival observed in cysLTR1-/- mice was associated with reduced granulomatous inflammation, reduced fibrosis and hepatocellular damage, impaired production of IL-4 in the liver, and reduced intracellular secretion of IL4 by CD4+ T cells and ILC2s in cysLTR1-/- mice compared with wildtype mice. Furthermore, we observed reduced granulomatous inflammation in the lungs of chronically infected cysLTR1-/- mice despite the heightened Th2 immune response in the lungs. Collectively, these data revealed that disruption of cysLTR1 leads to reduced granulomatous inflammation and reduced production of IL-4 in the liver during chronic schistosomiasis. In conclusion, the current study demonstrated both positive and negative roles for cysLTs signaling through cysLTR1 during different helminth infection models. Absence of cysLTR1 during N. brasiliensis leads to delayed expulsion of adult worms and impaired recall of memory responses, indicating that cysteinyl leukotriene signaling via cysLTR1 is essential for orchestrating host protective responses. On the other hand, signaling via cysLTR1 appears to be dispensable for the development of host protective responses during acute schistosomiasis in mice. However, mice deficient of cysLTR1 had reduced liver pathology during chronic schistosomiasis, suggesting that inhibition of this receptor could be a potential therapy for reducing granulomatous liver pathology.